KEBIJAKAN DAN KONFLIK PENDIRIAN RUMAH IBADAH DI INDONESIA - Nugroho, Nugroho (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2020)
A house of worship is one of the essential teachings of every religion because every religion has procedures for realizing human service to God who created it. Each religion has different processions of rituals from one another, according to the timing and naming of these rituals. Therefore, the aspect of worship and the aspect of a house of praying is an inseparable definition. This paper discusses the construction of places of worship from the point of view of religious politics implemented in state regulations. Government intervention in religious life is needed to regulate life to live in harmony and mutual respect. Government intervention has also been carried out by the Indonesian government during the colonial, post-colonial, old order, new order, up to now. It can be seen in the existence of regulations regarding the construction of places of worship as stipulated in SKB No. 01 / Ber / Mdn-Mag / 1969 and PBM number 8 and 9 of 2006. The regulations regarding the establishment of worship places in Indonesia have received various responses from religious groups, especially Islam and Christianity. Often these regulations also resulted in violence, arson, and the closure of places of worship. The arduous process to establish worship places is experienced by Muslims in eastern Indonesia. For Christians, the license requires the approval of a community of about 60 people is also difficult to gain.